Numerical Solution for Non-Stationary Heat Equation in Cooling of Computer Radiator System - Mhammad, Aree A.; Salh, Faraidun K. Hama; Abdulrahman, Najmadin W. (Sulaimani Journal for Pure and Applied Sciences, 2009)
In the paper a mathematical model is developed by using numerical solution to study the non stationary heat equation in one dimension. This model leads to incorporate a cooling system for a computer radiator. The result of the model is compared with the stationary heat transfer model. The simulation results show the performance of non stationary model in terms of variation of temperature.
Keywords: Cooling System Finite Difference Modelling Simulation NonStationary Heat EquationDimensionless Linear Partial Differential Equation LPDE